Differentiated therapy of patients with intracerebral complicated hemispheric ischemic cerebral stroke with secondary brainstem hemorrhages against the background of hypertensive - Dariy, V. I.; Sikorska, M. V.; Vizir, I. V.; Khramtsov, D.; Serikov, K. V.; Дарій, Володимир Іванович; Сікорська, Марина Володимирівна; Візір, Ірина Володимирівна; Серіков, Костянтин Вікторович (My University, 2025)
The purpose of the study is to assessment of the risk of secondary brainstem hemorrhages against the background of hypertensive encephalopathy in patients with intracerebral complicated hemispheric ischemic cerebral stroke using anticoagulant therapy. Was conducted a clinical and pathological study of 97 patients with intracerebral complicated hemispheric ischemic cerebral stroke aged 41 to 87 years. Of these, 55 were men (56,7%), average age 72,5±2,4; women 42 (43,3%), average age 76,5±2,1. Data on survival time and complications in the form of secondary brainstem hemorrhages directly correlated with the results of pathological changes in the brainstem. During autopsy of deceased patients with hemispheric ischemic cerebral stroke complicated by secondary hemorrhages of the brainstem who received anticoagulant therapy, in 12 cases (70,6%) out of 17, secondary massive hemorrhages in the brainstem were found, consisting of multiple hemorrhagic foci merging with each other. In individuals with hemispheric ischemic cerebral stroke who did not receive anticoagulant therapy, pathomorphologically, secondary massive hemorrhages in the brainstem were noted in only 12 (25,5%) of 47 deceased, while in 35 observations (74,5%), hemorrhages were determined in the form of individual hemorrhagic foci of small size or individual smallpoint hemorrhages, sometimes detected during macroscopic examination.
Keywords: ischemic cerebral stroke; secondary brainstem hemorrhages; hypertensive encephalopathy; anticoagulant therapy